Digital Image Correlation Analysis Of The Effects Of The Overlap Length, Adhesive Thickness And Adherends Yield Strength Over Similar And Dissimilar Joints Of High Strength Steel And Aluminum Alloys. (June 2018) - Bamberg, P.A.M.G.P.; Reisgen, U.; Schiebahn, A.; Barbosa, J.D.V.; Marx, B.; Coelho, R.S.
Abstract: This work encompasses the study of the mechanical behavior of single lap joints (SLJ) with similar and dissimilar materials, joined by epoxy adhesives. The objective was to analyze the effect of the variables overlap length (OL), adhesive thickness (AT) and adherends yield strength (YS) over the SLJ failure load (FL). The stress state of the joints was analyzed through an optical technique. Tensile tests were performed with samples containing three levels of the factors OL, AT and YS. This last variable analysis was performed using aluminum (AA5083 H111) and high strength steel (DP600) adherends, combined in three different levels – similar AA, similar HSS and dissimilar. The digital image correlation (DIC) technique was used in order to analyze and quantify the incidence of deformation on the adherends and adhesive during the tensile tests, in order to verify how the tensile load was distributed through the SLJ of this work. All the variables had significance over the SLJ. The OL increased the SLJ FL, but the effect reduced as the length is increased. The adherends YS also increased the SLJ FL, but not as much as the OL. Plastic deformation of the adherends leaded to the onset of high peeling stress, which reduced considerably the joints FL. The AT had a negative effect over the SLJ FL. This relationship varied when the adherends faced remarkable plastic strain.